HUBUNGAN ANTARA KEBIASAAN MEROKOK DAN KONSUMSI ALKOHOL DENGAN KEJADIAN HIPERTENSI PADA MASYARAKAT DI DESA TOUNELET - Winny Frisca Gloria Pandeiroot; Lucyana Pongoh; Christian Bertom Pajung (Yayasan Syalom Cipta Sumikolah, 2024)
Hypertension is a condition in which blood pressure in the body is too high. This excessive pressure gradually damages blood vessels, thereby disrupting blood flow throughout the body. Many factors contribute to hypertension, including smoking and alcohol consumption. Tounelet is a village in a district where most of the community has excessive smoking and alcohol consumption habits. The purpose of this study was to determine whether there is a significant relationship between smoking habits and alcohol consumption with hypertension cases in the community of Tounelet village. This research is a quantitative study using a cross-sectional study design. The sampling technique in this study used Accidental Sampling with a total of 100 respondents. The results of this study showed that 71% of respondents had a smoking habit and 74% consumed alcohol. Based on the research results, it can be concluded that there is a significant relationship between smoking habits and hypertension in the community of Tounelet village with a p-value obtained from the chi-square test of 0.000, and there is a significant relationship between alcohol consumption and hypertension cases in the community of Tounelet village with a p-value obtained from the chi-square test of 0.000.